MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS - Reskia Yofianti (Departemen Matematika, 2018)
The mathematical communications ability is one of the abilities that was expected to be developed in the learning of mathematics, but that occurs in school showed that students mathematical communication ability is stilllow. This was because students haven’t been actively in volved in the learning so that in teraction in the classwasn’t optimal. One effort that can be done was applying cooperative learning model type TTW. The purpose of this study was know the differences between students mathematical communication ability using learning model of cooperative type TTW with those whole arning directly. This study was combination of quasy experiment and descriptive study with static group design. The instrument of this study wer equiz and test of mathematical communication ability in the form of essay matter. The results showed that the mathematical communication ability of students using cooperative model of TTW type is better than those who learning using direct learning in class VIII SMPN 12 PadangKeywords – Cooperative learning,TTW, mathematics communication skills, Direct Instruction